Participation in water resources management in Latin America 2017-2022: A systematic review - Ochoa Valer, Jesus (Seven Editora, 2023)
This article addresses a systematic review of research for Latin America on stakeholder participation in water resource management, considering the fragility of this resource, added to the processes of climate change and variation, which, if not addressed in a concerted manner (participatory management), implies a crisis in governance that could worsen with serious effects on ecosystems, including human beings. The objectives of this article focus on characterizing where (country) the articles included in this analysis were developed, establishing the methodological approach, technique, and instrument used, and analyzing the results of the articles reviewed on participation in water resources management for Latin America. The methodology corresponds to a systematic review article using the Prisma statement of articles selected from the databases: Dialnet, EBSCO, Redalyc, SciELO, and Scopus. The conclusions reached show that public management processes have been incorporating participation as mechanisms through which users and civil society are involved, as well as social control mechanisms, to achieve sustainable management of water resources.DOI: https://doi.org/10.56238/devopinterscie-144